(untitled) (WidyaAmrita: Jurnal Manajemen, Kewirausahaan dan Pariwisata, 2024)
The aim of this research is to determine the role of job satisfaction in mediating the influence of service quality on consumer loyalty, both directly and indirectly, so it is important for Wijaya Cellular Bali to pay attention to this. The research method in this study uses observation, interviews, documentation, literature study and questionnaires. A questionnaire distributed to 96 sample people from Wijaya Cellular Bali. The analysis technique used is path analysis. Based on the research results, it was concluded that service quality has a positive and significant effect on consumer satisfaction at Wijaya Cellular Bali. Service quality has a positive and significant effect on consumer loyalty to Wijaya Cellular Bali. Consumer satisfaction has a positive and significant effect on consumer loyalty to Wijaya Cellular Bali. Service quality has a positive and significant indirect effect on consumer loyalty through consumer satisfaction. Thus, consumer satisfaction acts as a partial mediator in the influence of service quality on consumer loyalty. Suggestions For future researchers, it is recommended to add other variables such as consumer trust and marketing mix so that the research results are more varied and produce better research